ANALISIS PROFITABILITAS DALAM MEMODERASI LIKUIDITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN PADA SEKTOR FARMASI TAHUN 2020-2023 - Muzaqi, Ahmad; Wahyuni, Ika; Nanggala, Ardhya Yudistira Adi (Fakultas Ekonomi dan Bisnis, 2025)
The results of the research test using the Smart Partial Least Squares (PLS) application showed that Liquidity has a positive but insignificant effect on Company Value. Leverage has a positive but insignificant effect on Company Value. Profitability has a positive but insignificant effect in moderating the effect of Liquidity on Company Value. Profitability has a positive but insignificant effect in moderating the effect of Leverage on Company Value.